Constitutional politics in a conservative era - Sarat, Austin (JAI, 2008)
This volume of "Studies in Law, Politics, and Society" presents a unique special issue "Constitutional Politics in a Conservative Era". This issue brings together the work of leading scholars of Constitutionalism, Constitutional law, and politics in the United States to take stock of the field to chart its progress, and point the way for its future development. Much of the way Americans have thought about Constitutional law has, until recently, been dominated by models developed during the Warren Court Era. Today, however, scholars seek new approaches, approaches that do not take for granted liberal hegemony in the courts. Among these, theories of popular constitutionalism and judicial minimalism appear to be increasingly popular. How should Scholars think about American courts in an era of conservative domination of the judiciary? What should/will constitutional politics in the United States look like over the next decade?
Keywords: Sociological jurisprudence.; Law -- Political aspects.; Constitutional law -- United States.; Law -- Political aspects -- United States.; Conservatism -- United States.; Political science & theory.; Political Science -- History & Theory.; United States -- Politics and government -- 1989-; elektronické knihy; electronic books